The behavioral benefits of proper ambient luminaire layouts in Alzheimer’s homes and supplemental light therapy administration - Geiger, Laura (Kansas State University, 2011)
Over 26.6 million people suffer from Alzheimer's Disease in the United States, and while no cure exists, how their built environment is illuminated - lamp type, color selection, wavelengths emitted, luminaire specifications, and luminaire layout - may enhance the lives of Alzheimer's patients (APs), their relatives, and caretakers. Research has found mixed results when it comes to selecting the correct lamp, but most researchers agree illumination levels benefit APs quality of life. Achieving higher illumination levels can be achieved by adding more luminaires to the ambient lighting layout, placing additional task lighting in specific locations, or using light therapy. Exposing APs to higher illumination levels can have positive behavioral benefits and help shift the circadian rhythm. Common problems such as aggression, sleepiness, and agitation can be reduced if proper lighting layouts or light therapy is used on a consistent basis. Adding to research, several Alzheimer’s facilities in Kansas and Colorado were contacted to complete questionnaires about their lighting and resident’s behaviors. Upon analysis, these facilities concurred with research about lamp types, daylight, and luminaire layouts showing higher levels of illumination were preferred by APs and also where they displayed their best behaviors. Ninety percent of facilities agreed that APs enjoyed sitting by the windows, and over half agreed APs exhibited better behavior while seated here. Homes with CLFs documented APs were typically more calm and happy than those with tubular fluorescents, but the conclusions made need additional research to support the findings.
Keywords: Alzheimer's; Light therapy; Daylight; Circadian rhythm; Architectural engineering (0462)